FORMULASI DAN EVALUASI GRANUL EFERVESEN EKSTRAK DAUN SALAM (SYZYGIUM POLYANTHUM (WIGH) WALPERS) - Akbar, Nanda Dwi Akbar; Rizky Uswatun Arifah, Anisya; Setyaningsih, Wahyu; Putri Pitarisa Sudarsono, Agustina (School of Pharmacy Institut Teknologi Bandung, 2025)
Bay leaves (Syzygium polyanthum (Wigh) Walpers) contain flavonoid compounds which act asantioxidants for the treatment of diabetes mellitus. The ethanol extract of bay leaves can reduceblood glucose levels in white rats that have been induced by streptozotocin. Effervescentgranules dissolve easily in water and provide a fresh taste like fizzy drinks making it easier toconsume, especially for consumers who cannot take capsules or tablets. The aim of this researchwas to formulate and evaluate bay leaf extract effervescent granules. The research stage wasbegun by producing bay leaf extract by maceration. The effervescent granule formulation wasmade in 3 formula that contain 1% bay leaf extract, citric acid, tartaric acid, sodium bicarbonate,aspartame, magnesium stearate, talc, lactose and PVP K-30 concentrations of 2% (F1), 4% (F2),and 5% (F3). Effervescent granules were prepared by dry granulation. The physical propertiesof bay leaf extract effervescent granules that were observed included organoleptic, watercontent, flow time, angle of repose and effervescent cessation time. The results showed that F1had the greatest water content (2.485%), flow time (10.274) and angle of repose (24.70), but F3had the greatest effervescent cessation time (4.1 minutes) compared to F1 (3, 3 minutes) and F2(3.5 minutes). This research can be concluded that effervescent granules containing 1% bay leafextract and PVP K-30 with varying concentrations of 2, 4 and 5% meet the requirements forwater content, flow time, angle of repose and effervescent cessation time.